2010
DOI: 10.1111/j.1472-765x.2010.02926.x
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic resistance patterns and sequencing of class I integron from uropathogenic Escherichia coli in Lebanon

Abstract: Aim:  To study the prevalence and molecular basis of antimicrobial resistance in UPEC. Methods and Results:  PCR was used to detect the presence of the Class I integron variable region (VR). The VR amplicons were then characterized by partial sequencing and restriction digestion with AluI. VR negative isolates showed more antibiotic susceptibility than VR positive isolates. 30% of the isolates were positive for the VR and carried the genes dfrA7, dfrA17‐aadA5, dfrA1‐aadA1, dfrA12‐orf5‐aadA2 and blaOXA‐30‐aadA1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
14
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 21 publications
8
14
0
Order By: Relevance
“…Sequencing analysis of the cassette arrays revealed a predominance of the dfrA17 and dfrA17-aadA5 arrays in this population. This finding agrees with those of previous studies reporting a strong association between class 1 integrons and the dfrA and aadA cassettes [15,33]. Indeed, the dfrA17 and aadA5 cassettes were formerly found in a class 1 integron of an E. coli isolated in 1998 from the urinary tract of an Australian patient [34].…”
Section: Molecular Characterization Of Gene Cassettessupporting
confidence: 83%
“…Sequencing analysis of the cassette arrays revealed a predominance of the dfrA17 and dfrA17-aadA5 arrays in this population. This finding agrees with those of previous studies reporting a strong association between class 1 integrons and the dfrA and aadA cassettes [15,33]. Indeed, the dfrA17 and aadA5 cassettes were formerly found in a class 1 integron of an E. coli isolated in 1998 from the urinary tract of an Australian patient [34].…”
Section: Molecular Characterization Of Gene Cassettessupporting
confidence: 83%
“…Sequencing the variable region of class 1 and 2 integrons from MDR- and XDR-UPEC strains revealed the presence of genes encoding the antibiotic modifying enzymes aad A1, aad B, aac C, ant 1, dfr A1, and dfr A17. MDR- and XDR-UPEC strains with resistance to SXT and GM antibiotics were mainly associated with class 1 and 2 integrons, as described by other authors (Solberg et al, 2006; Márquez et al, 2008; El-Najjar et al, 2010; Soleimani et al, 2014; Acosta-Pérez et al, 2015; Yahiaoui et al, 2015). Class 3 integrons are part of the soil/freshwater proteobacteria group, have a poor occurrence rate and were not identified in this study (Deng et al, 2015).…”
Section: Discussionsupporting
confidence: 63%
“…In our research, class 1 and 2 integrons were detected in 50.9% of the isolates. El-Najjar et al [26], in 2010, showed that of 100 E. coli isolates collected from patients, 30 had class 1 integrons. In our study, 24 (47.05%) of the isolates carried class 1 integrons, found in 50.9% of the MDR isolates.…”
Section: Discussionmentioning
confidence: 99%